Stolen dreams : a Manchurian legacy - Kowalska Sormark, Julie (2019)
Vladislav Kowalski was relentless in his pursuit of establishing a timber business in Harbin, Manchuria. This account by his granddaughter blends family stories and photos with extensive work in many archives and libraries